Terrestrial ciliate assemblages from Iguazú National Park (Argentina) under contrasting environmental scenarios - Pascualat, Agostina (2024)
Bryophytes and lichens provide organic nutrients and a moist environment for the development of microbial communities. Ciliates show adaptations to inhabit these biotopes where water availability is crucial, like forming resting cysts under unfavorable conditions. To identify possible drivers of these terrestrial ciliate communities, we analyzed the taxonomic richness and composition in two paths from Iguazú National Park (Circuito Inferior, near waterfalls; Sendero Macuco, away from cascades), during wet and dry periods, in samples composed of bryophytes or bryophytes + lichens growing on trees or rocks. The non-flooded Petri dish and optical microscopy methods were used. A total of 132 ciliates were found, mostly Spirotrichea and Colpodea. Taxonomic richness differed between paths (GLMM, p = 0.05), being 1.4 times higher in Sendero Macuco, which had more exclusive taxa than Circuito Inferior. Likewise, ciliate assemblages were influenced by habitat conditions and sample composition (NMDS, ANOSIM test p < 0.01). Bryophytes and lichens were dampened by the waterfall’s spray in Circuito Inferior during the wet period when higher richness was observed. In Sendero Macuco, higher richness occurred during the dry period, suggesting these differences could be related to contrasting habitats instead of climatic conditions. Nevertheless, C/P indices revealed a prevalence of the r-selected Colpodea over the K-selected Spirotrichea + Heterotrichea in both paths during the dry period, indicating unstable environmental conditions. Further research is needed to deepen our knowledge on terrestrial ciliates in this natural protected area from South America, which is a world hotspot for biodiversity.